Some properties of certain classes of p-valent functions defined by the Hadamard product - M. K. Aouf; T. M. Seoudy (Հայաստանի ԳԱԱ)
In this paper we obtain sandwich type theorems, inclusion relationships, convolution properties and coefficient estimates of certain classes of p-valent analytic functions defined by a convolution. Several other new results are also obtained.
Keywords: Mathematics; Science